Testing Reliability of Biophilic Design Matrix Within Urban Residential Playrooms - Marte, Ellen; Calumpit, Abigail; de Sá Bessa, Bárbara; Toledo, Ashley; Fadda, Roberta; Skoler, Tricia (Frontiers in Psychology, 2020)
Playtime in urban cities has become an indoor activity for children due to limited access to natural outdoor environments. This product of urbanization makes the case for the introduction of biophilic design. However, playrooms are often neglected as a possibility in designing a natural space indoors. Interior designers and other specialists lack a reliable tool to identify and incorporate biophilic features into the design of these indoor environments in urban settings. The Biophilic Interior Design Matrix (BID-M) developed by McGee and Marshall-Baker quantifies 52 of Kellert’s biophilic design attributes to assess their presence and absence within interior spaces. We expanded its use by testing the matrix in a new type of space, urban playrooms, and coded images of 45 children’s playrooms within Manhattan residential buildings in New York City, including assessing a larger sample and reliability rate compared to McGee and Marshall-Baker’s research. Inter-rater reliability of the overall design matrix and individual matrix items was measured with percent agreement and free-marginal multirater kappa. Reliability testing showed overall good reliability of the overall design matrix. Several matrix items had low reliability between raters. Our findings show that the BID-M needs to be modified to better assess urban interior spaces for children.